Integrated natural resource management research in the CGIAR: a brief report on the INRM Workshop held in Penang, Malaysia, 21-25 August 2000 (CGIAR System Organization, 2000)
CGIAR system-wide meeting on integrated natural resource management (INRM). The second was held from 20-25 August 2000, at the new headquarters of ICLARM in Penang, Malaysia. Convened by the Centre Directors Natural Resouce Managemnet Task Force, four dozen scientists from 13 of the 16 CGIAR centres and their partner institutions discussed integrated natural resource management in relation to the CGIAR's research program. This report summarises some of the issues discussed at that meeting. The participants sought to share knowledge and strengthen cooperation in carrying out INRM research in the CGIAR. The most important outcome was greater elucidation of ways to assess the impact of INRM research in relation to the five forms of capital (natural, human, social, financial and physical). It was strongly agreed that impact assessment in an integral part of all INRM research, and is essential to provide the feedback necessary for sound, adaptive management of natural resources. Measures selected to assess impact are not absolute but must be decided through negotiations by stakeholders. This is significantly different from how the CGIAR has generally assesed impact. At the Penang meeting, the participants discussed the conceptual underpinnings of INRM as well as how it might be undertaken or expanded to help the CGIAR fulfill its mission of improving food security and reducing poverty without causing lasting damage to the environment. Topics of discussion included the need to shift from empirical to process-oriented research and to use system approaches, to focus on ways of making ecosystems and natural resources managers such as farmers and others more capable of adapting positively in response to change, to work at multiple scales, and to suggest ways of dealing with the tradeoffs that are inevitable in various resource management options. Also examined was how INRM research can enhamce the impact of germplasm improvement, which has been the core of the CGIAR's success for three decades. Several case studies from Asia, Africa and Latin America were presented at the meeting to illustrate how INRM research has successfully addressed real-life problems..